2014
DOI: 10.1017/s175173111300219x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of caspase-9 and its influencing factors in beef during conditioning

Abstract: To study the activation of caspase-9 and its potential influence in conditioning, longissimus thoracis (LT), semitendinosus (STN) and psoas minor (PMi) muscles were used to analyze the ratio of pro-apoptotic bax to anti-apoptotic bcl-2 in fresh tissues and observe the changes in ATP, cytosolic cytochrome c and caspase-9 activity levels during storage at 4°C. Caspase-9 activity at 5 h is higher than the activity at 0 and 24 h in the muscles ( P < 0.001). The ATP content decreased between 0 and 3 h, between 8 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The fragments of myofibrillar proteins in gel were identified according to the molecular weight of standard proteins. The intensities of bands were quantified by Quantity One Software (Bio-Rad Laboratories, Philadelphia, PA, USA); Electrophoresis procedures were implemented by our previous work [15]. Actin was defined as the internal standard.…”
Section: Myofibrillar Proteins Preparation and Sodium Dodecyl Sulfate-polyacrylamide Gel Electrophoresis (Sds-page)mentioning
confidence: 99%
See 1 more Smart Citation
“…The fragments of myofibrillar proteins in gel were identified according to the molecular weight of standard proteins. The intensities of bands were quantified by Quantity One Software (Bio-Rad Laboratories, Philadelphia, PA, USA); Electrophoresis procedures were implemented by our previous work [15]. Actin was defined as the internal standard.…”
Section: Myofibrillar Proteins Preparation and Sodium Dodecyl Sulfate-polyacrylamide Gel Electrophoresis (Sds-page)mentioning
confidence: 99%
“…The expression levels of desmin bands were assayed by SDS-PAGE and Western blotting according to our previous study [15] with slight modification. After electrophoresis, proteins were transferred to polyvinylidene fluoride membranes (Immobilon-P, Millipore, MA, USA).…”
Section: Immunoblotting For Desminmentioning
confidence: 99%
“…Cao et al . () also found the increase in cytosolic cytochrome c in PM beef skeletal muscles and believed that it was responsible the increase in caspase‐9 activity. In comparison with control, the level of cytochrome c in the Ca 2+ ‐injected samples increased markedly, as determined by Western blotting (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…The rise possibly resulted from the release of cytochrome c from mitochondria to cytoplasm, which has been demonstrated by examining the cytochrome c levels in subcellular fractions of the mitochondria and cytoplasm (Huang et al, 2016). Cao et al (2014) also found the increase in cytosolic cytochrome c in PM beef skeletal muscles and believed that it was responsible the increase in caspase-9 activity. In comparison with control, the level of cytochrome c in the Ca 2+ -injected samples increased markedly, as determined by Western blotting (Fig.…”
Section: Effect Of Injection Treatment On Cytochrome Cmentioning
confidence: 87%
“…Tenderness is one of the most important characteristics of meat quality; adequate meat tenderness has been considered as the major contributor to consumer satisfaction, and repetition for purchase of meat (Moeller et al., ; Sionek & Przybylski, ). The main factors involved in meat tenderness and postmortem changes in muscle are proteolysis, fragmentation and subsequent weakening of the myofibrillars and connective tissue (Delbarre‐Ladrat, Cheret, Taylor, & Verrez‐Bagnis, ), loss in integrity of muscle cell (Cao et al., ; Zhang et al., ; Zheng et al., ; Zhou, Wang, Pan, Sun, & Cao, ), and ultimately tenderization of meats (Lonergan, Zhang, & Lonergan, ).…”
Section: Introductionmentioning
confidence: 99%